2007
DOI: 10.1080/10942910600627996
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Characteristics of Carob Pekmez

Abstract: This study investigated the physicochemical properties and rheological behavior of carob pekmez. Rheological measurements were undertaken at 30, 40, 50, 60, and 70°C using a rotational viscometer at the shear rate of 5, 10, 20, 50, and 100 1/s. The flow characteristics of carob pekmez were described by the power law and Herschel-Bulkley models. The HerschelBulkley model was found to be the best to describe the rheological property with the coefficient of determination higher than 0.998. Carob pekmez exhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 23 publications
3
28
0
4
Order By: Relevance
“…Simsek and Artık (2002) reported that the titratable acidity values of grape, mulberry and fig were 0.74, 0.50 and 1.01%, respectively. In a different study the titratable acidity of carob molasses was reported as 0.60% (Sengul et al, 2007). Water activity values of both molasses were similar (p > 0.05).…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Simsek and Artık (2002) reported that the titratable acidity values of grape, mulberry and fig were 0.74, 0.50 and 1.01%, respectively. In a different study the titratable acidity of carob molasses was reported as 0.60% (Sengul et al, 2007). Water activity values of both molasses were similar (p > 0.05).…”
Section: Resultsmentioning
confidence: 78%
“…Similarly, found that pH and soluble solid values of juniper molasses were as 5.21 and 75.2%, respectively. pH values of carob molasses (Sengul, Ertugay, Sengul, & Yüksel, 2007), grape and fig molasses (Simsek & Artık, 2002) were stated as 5.09, 5.26 and 4.78, respectively. In general, soluble solid content of molasses samples was reported as 72% for carob molasses (Sengul, Ertugay, Sengul, & Yüksel, 2007), 75.46 and 67.08% for black grape and mulberry molasses (Yogurtçu & Kamış lı, 2006) 72.4% for sweet sorghum molasses (Akbulut & Ozcan, 2008) and 75.2% for juniper molasses in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of temperature on the flow behavior of fluid foods can be described by the Arrhenius-type relationship (Gundurao, Ramaswamy, & Ahmed, 2011;Ibarz et al, 1996Ibarz et al, , 1994Ibarz, Gonzalez, et al, 1992;Kaya & Belibaǧlı, 2002;Sengül, Ertugay, Sengül, & Yüksel, 2007):…”
Section: The Effect Of Temperaturementioning
confidence: 99%
“…Molasses contains carbohydrates, minerals, organic acids, proteins, flavonoids and phenolic compounds which make it a very beneficial product for human nutrition (Sengül et al, 2007;Karababa and Isikli, 2005). Carob fruit (Ceratonia Siligua) is also known as locust bean and has a high content of carbohydrates 45 % (sucrose 30 % or more), protein 3 % and low levels of fat 0.6 % (Sengül et al, 2007;Santos et al, 2005). Carob molasses is a thick syrup and is used as an alternative to jam, sugar or honey.…”
Section: Introductionmentioning
confidence: 99%